Strategi Komunikasi Es Kopi Kulu Dalam Meningkatkan Brand Awareness Studi Kasus Kedai Kopi Kulumanu Kota Tangerang - Muhammad Wildan Aziz (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
This analysis delves deeply into Es Kopi Kulu's communication strategy to enhance brand awareness, employing a qualitative descriptive research method through literature review. Es Kopi Kulu has successfully crafted a brand identity through innovative products that showcase creativity and align with current consumer trends. The strategic use of social media has been pivotal in expanding reach and fostering customer interaction, involving them in participatory activities and sharing personal stories. Additionally, collaborative approaches and sponsorships with third parties, such as local artists, have contributed to reinforcing brand awareness within the community. Collectively, the synergy of these three elements provides Es Kopi Kulu with an edge in creating a consistent brand narrative and cultivating strong relationships with customers. This achievement serves as an inspirational catalyst for industry players to tap into creativity, leverage social media effectively, and form strategic partnerships to fortify brand awareness in a competitive market